What are you looking at? : the surprising, shocking, and sometimes strange story of 150 years of modern art - Gompertz, Will, 1965- (Dutton, 2012)
"We all know what Modern Art looks like. We've seen Monet's water lilies, we've admired Picasso's nudes, and we've gawked at Damien's shark, as well as the price tag. But what does it all mean? What is Modern Art? Who started it? Why do we love/hate it? And why is it such big money? What Are You Looking At? takes the reader on a captivating tour of modern art from Impressionism to the present day, telling the story of the movements, the artists and the wonderful works that not only changed art forever, but helped create and define the modern world. "--